(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
The history of medicine reflects the development of human civilization and scientific thought. From primitive healing rituals to evidence-based clinical practice, medicine has evolved through centuries of observation, experimentation, and innovation. Ancient civilizations such as Mesopotamia, Egypt, Greece, and the Islamic Golden Age made significant contributions to medical knowledge that continue to influence modern healthcare systems.